Relationship between hyperventilation syndrome and anxiety disorders in women-internally displaced persons with threatened miscarriage - Romanenko, I. Yu.; Romanenko, I. V.; Romanenko, Yu. I.; Glushchenko, V. R.; Romanenko, V. I.; Zaitsev, M. A. (Journal of Education, Health and Sport, 2020)
Abstract The protracted armed conflicts create not only political, legal, socio-economic problems, form the migration flows of the population, but also affect the somatic and mental health of people. Pregnancy is a critical stage in the development of a woman’s personality. According to recent studies, about 54% of women during pregnancy experience anxiety, the prevalence of hyperventilation syndrome (HVS) in population is 6-9.5%. The aim of the study was to determine the prevalence of hyperventilation syndrome and to establish its relationship with anxiety disorders in women - internally displaced persons with threatened miscarriage, living in the Luhansk region to improve treatment measures and prevent obstetric and perinatal complications. Material and Methods. The study included 35 pregnant women - IDPs who were hospitalized regarding threatened miscarriage to the hospitals, located in the Luhansk region (group I). The control group consisted of 30 pregnant women with non-complicated obstetric anamnesis and physiological course of pregnancy with similar gestational period of pregnancy and place of residence. Spielberger State-Trait Anxiety Inventory was used to assess the level of anxiety, the Nijmegen questionnaire was used to identify the manifestations of HVS. Results and discussion. Manifestations of HVS were observed in 8.57 % of patients of group I, in group II were not recorded. Patients of group I had significantly higher levels of state and trait anxiety, HVS. In group I a positive correlations between the indicators of HVS and indicators of state and trait anxiety were found. Conclusions. Antenatal study of levels of anxiety, manifestations of HVS in pregnant women - IDPs with threatened miscarriage will allow to individualize the approach to the management of pregnancy and if needed to timely develop rehabilitating measures, that will contribute to a successful outcome of the pregnancy and affect the health of the mother and her offspring.